Two cases of lung neuroendocrine carcinoma with carcinoid morphology - Kenji Inafuku; Tomoyuki Yokose; Hiroyuki Ito; Daisuke Eriguchi; Joji Samejima; Takuya Nagashima; Haruhiko Nakayama; Masaki Suzuki; Kouzo Yamada; Munetaka Masuda (BMC, 2019)
Abstract Background The category of grade 3 neuroendocrine tumor (NET G3) was newly introduced in the 2017 World Health Organization (WHO 2017) classification of neuroendocrine neoplasms of the pancreas. Pancreatic NET G3 shows a carcinoid-like morphology with high proliferative activity and the prognosis is intermediate between NET G2 and neuroendocrine carcinoma. There is no category corresponding to NET G3 in the current WHO 2015 classification of lung tumors. Herein, we report two cases of lung neuroendocrine carcinoma with carcinoid morphology that correspond to NET G3. Case presentation Case 1: An abnormal chest shadow was detected in a 78-year-old female never-smoker during a routine medical examination. She was asymptomatic. The radiological assessment revealed a mass in the peripheral S4 segment of the right lung. She underwent right middle lobectomy for the mass preoperatively diagnosed as non-small cell lung carcinoma. Postoperative histological examination revealed a neuroendocrine tumor with carcinoid morphology and a mitotic count of 15/2 mm2. Case 2: An abnormal chest shadow was detected in a 74-year-old female never-smoker undergoing follow-up for another disease. She was asymptomatic. The radiological assessment revealed a mass in the peripheral S3 segment of the right lung. She underwent right upper lobectomy for the mass suspected to be lung carcinoma. Postoperative histological examination revealed a neuroendocrine tumor with carcinoid morphology with mitotic count of 13/2 mm2. Both of these tumors showed carcinoid morphology but with a mitotic count exceeding 10/2 mm2; thus, we diagnosed them as small cell lung carcinomas according to the current WHO 2015 classification. Conclusions Our tumors occurred in female never-smokers and their histology showed carcinoid morphology without extensive necrosis. Moreover, proliferative abilities of them were extremely low compared to small cell lung carcinoma. The clinical and pathological features of our tumors appeared to be different from those of small cell lung carcinoma. Although there is no category corresponding to NET G3 in the current classification of lung tumors, we consider that our tumors may correspond to NET G3 and identification of this subset is relevant for therapeutic management.